2019
DOI: 10.1017/s1355770x19000081
|View full text |Cite
|
Sign up to set email alerts
|

Wildlife trade and consumer preference for species rarity: an examination of caged-bird markets in Sumatra

Abstract: This study examines conservation effects of wildlife trade using demand and supply data from caged-bird markets in Sumatra, Indonesia. When consumers have a strong preference for species rarity, trade could result in wildlife overexploitation and species extinction. Results from a choice experiment show that buyers of caged birds indeed value species rarity. However, not all rare species are equally preferred. Species that are frequently traded lose their rarity value, even if rare in the wild. Analysis of tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…the type of vendor and the character of its store, the season, current trends, customer preferences, the time of day a survey is conducted, etc. (Burivalova et al 2017, Krishna et al 2019, Marshall et al 2019. As a result, and as this study has shown, precise outcomes delivered by DCM cannot therefore be expected.…”
Section: Discussionmentioning
confidence: 78%
“…the type of vendor and the character of its store, the season, current trends, customer preferences, the time of day a survey is conducted, etc. (Burivalova et al 2017, Krishna et al 2019, Marshall et al 2019. As a result, and as this study has shown, precise outcomes delivered by DCM cannot therefore be expected.…”
Section: Discussionmentioning
confidence: 78%
“…Conversely, the prevalence (Marshall et al, 2020a) and abundance of highly sought‐after taxa (e.g. White‐rumped Shama, Oriental Magpie‐robin, leafbirds) kept by contestants suggests that an anthropogenic Allee effect (Courchamp et al., 2006) is at work, drawing some species into an extinction vortex through their ever‐increasing rarity in the wild, market value and status‐giving properties (Eaton et al., 2015; Krishna et al., 2019). Although breeders show similar behaviours and preferences to contestants, they also favour profitable taxa (lovebirds, canaries Serinus spp., doves) that can be easily bred and resold for a much‐elevated price.…”
Section: Discussionmentioning
confidence: 99%
“…To estimate losses of birds, we calculated the proportion of them owned in 2016 that respondents reported to have subsequently died. As the owning of trafficked wildlife is not illegal under Indonesian legislation (Chng et al, 2018) our questions did not relate to perceived illegal behaviour; thus in common with previous research into songbird-keeping (Burivalova et al, 2017;Krishna et al, 2019) we assumed that respondents provided information about the origins of their birds truthfully.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals' also obtain relatively higher satisfaction from experiential versus material consumption (Gilovich, Kumar and Jampol, 2015). (Krishna et al, 2019). 3 In the case of vagrant birds, rarity takes a different meaning as the value attached to experiencing a rarity increases with the fewer individuals who manage to experience it.…”
Section: Sightings Involving a Potential New Taxon (Species Or Sub-species) If The Id Is Accepted Then The Record Is Forwarded To The Boumentioning
confidence: 99%